Design and Development of the Strategic Plan of the Handball Federation of Iran - Jamshidi , Arefeh; Soltani, Mostafa; Asghari , Zahra; Heydari, Erfan (Journal of Foresight and Health Governance, 2026)
The present study is classified as qualitative research in terms of research method. Regarding its objective, this research is applied, and considering the nature of the subject, it falls within the field of strategic studies. In terms of data collection method, the present study is a combination of field studies and a descriptive–analytical approach. The statistical population of the quantitative section included 580 coaches, players, referees, and related staff members; the sample size was estimated at 234 individuals based on the Krejcie and Morgan table, and participants were selected through stratified random sampling. The data collection instruments included the review of documents as well as library and internet resources, semi-structured interviews with managers and experts associated with the Handball Federation of Iran, and a researcher-made questionnaire. To prioritize the factors, the Friedman test was applied, followed by the Internal Factor Evaluation (IFE) and External Factor Evaluation (EFE) matrices within the framework of SWOT analysis. The findings indicated that the EFE score was 2.44 and the IFE score was 2.48; therefore, the strategic position of the Federation was located in the WT quadrant, indicating the necessity of adopting defensive strategies to reduce weaknesses and mitigate the effects of threats. Accordingly, a set of strategies was formulated in four categories: SO, WO, ST, and WT. The results of this study demonstrated that the Handball Federation of Iran needs to focus on reducing internal weaknesses and addressing environmental threats in order to improve its position. Implementing the proposed strategies in the areas of infrastructure improvement, human resource development, and strengthening international interactions can facilitate the path toward growth and enhanced performance of the Federation.